2015
DOI: 10.1037/cou0000063
|View full text |Cite
|
Sign up to set email alerts
|

Forgiving the self and physical and mental health correlates: A meta-analytic review.

Abstract: Self-forgiveness has been conceptualized as a coping strategy that may improve health and well-being. To better understand the functions of self-forgiveness, this meta-analysis examines the correlates of self-forgiveness associated with physical and mental health. For physical health, across 18 samples and 5,653 participants, the correlation was .32. For psychological well-being, across 65 samples and 17,939 participants, the correlation was .45. To augment this primary focus on physical and mental health corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 41 publications
5
106
1
7
Order By: Relevance
“…In their meta-analysis, Davis et al (2015) concluded that, although the self-reported evidence for the relationship between self-forgiveness and physical and mental health is compelling, some limitations need to be addressed. Davis et al (2015) observed that most studies focused on trait self-forgiveness, recommending that state self-forgiveness term, if one is unforgiving toward others, cardiac health consequences could occur.…”
Section: Self-forgivenessmentioning
confidence: 96%
See 1 more Smart Citation
“…In their meta-analysis, Davis et al (2015) concluded that, although the self-reported evidence for the relationship between self-forgiveness and physical and mental health is compelling, some limitations need to be addressed. Davis et al (2015) observed that most studies focused on trait self-forgiveness, recommending that state self-forgiveness term, if one is unforgiving toward others, cardiac health consequences could occur.…”
Section: Self-forgivenessmentioning
confidence: 96%
“…Davis et al (2015) observed that most studies focused on trait self-forgiveness, recommending that state self-forgiveness term, if one is unforgiving toward others, cardiac health consequences could occur.…”
Section: Self-forgivenessmentioning
confidence: 96%
“…1). Psychologische Faktoren, die die Bereitschaft zur Vergebung moderieren, sind unter anderem Neigung zur Rache, negativ getönte Affektivität, geringe Lebenszufriedenheit, Empathie, Scham-/Schuldneigung, Selbsterkenntnis in eigenes Fehlverhalten, Selbstwertgefühl [McCullough et al, 2001;Wade et al, 2008;Exline et al, 2008;Allemand und Steiner, 2010;Kämmerer, 2011;Davis et al, 2015b].…”
Section: Empirische Befunde Zu Psychologischen Bedingungen Und Vorausunclassified
“…This result contradicted previous primary studies (cf. Maltby et al, 2001;Mauger et al, 1992, and a metaanalysis (Davis et al, 2015a) with the latter one suggesting a significant negative association between self-forgiveness and psychological distress, especially depressive and anxiety symptoms. However, these studies did not consider the process-oriented self-forgiveness approach, but rather considered self-forgiveness as an endpoint (i.e., considering higher scores as forgiveness and lower scores as a failure to forgive) without considering process to reach self-forgiveness.…”
Section: Removed Not-specified and Predicted Pathsmentioning
confidence: 99%
“…Psychological benefit of forgiveness has received a great attention in the forgiveness literature, and much forgiveness research has found the association of forgiveness with psychological distress, especially depressive and anxiety symptoms (for a meta-analysis, see Davis et al, 2015a). In the literature of internalized problems such as depression and anxiety, many researchers explain these symptoms in a broad context considering vulnerability factors such as temperament, emotion and information processing, emotion regulation, and selective attention (e.g., Beck, Emery, & Greenberg, 1985;Durbin & Shafir, 2008;Flynn & Rudolph, 2010;Krueger, 1999).…”
Section: Self-forgiveness and Anxiety And Depressionmentioning
confidence: 99%